2016
DOI: 10.1016/j.jallcom.2015.12.167
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature growth of (100)-oriented Ba(Zr0.2Ti0.8)O3- 0.5(Ba0.7Ca0.3)TiO3 thin films using a LaNiO3 seed layer

Abstract: Low-temperature growth of Ba(Zr 0.2 Ti 0.8)O 3-0.5(Ba 0.7 Ca 0.3)TiO 3 (BZT-0.5BCT) films, at temperatures as low as 550 °C, was successfully achieved by a sol-gel route using a LaNiO 3 seed layer. The influence of the seed layer on the crystallization behavior and electric properties of the films was investigated in detail. It was found that low interfacial diffusion and high (100) orientation were simultaneously achieved by introducing a seed layer between films and substrates. Low leakage current density wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It is clear that maximizing the piezoelectric response, electrode-active areas, and mechanical deformation in thick, robust, and defect-free piezoelectric thin film layer stacks is imperative for highperforming PEHs. Although BCZT thin films have been realized using chemical [12,13] and physical [14][15][16] deposition methods, processing µm thick films remains a major challenge as they display a high propensity for cracking when mechanically stressed [17][18][19]. Because thin films are restricted by the substrate, they are often subject to a considerable amount of residual stress (σ R ) after processing.…”
Section: Of 13mentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that maximizing the piezoelectric response, electrode-active areas, and mechanical deformation in thick, robust, and defect-free piezoelectric thin film layer stacks is imperative for highperforming PEHs. Although BCZT thin films have been realized using chemical [12,13] and physical [14][15][16] deposition methods, processing µm thick films remains a major challenge as they display a high propensity for cracking when mechanically stressed [17][18][19]. Because thin films are restricted by the substrate, they are often subject to a considerable amount of residual stress (σ R ) after processing.…”
Section: Of 13mentioning
confidence: 99%
“…Platinized silicon is perhaps the most industrially relevant platform for thin-film piezoMEMS development today. A thin layer of (001)-oriented LaNiO 3 (LNO) is commonly added as a seed oxide electrode to promote (001)-orientation and the piezoelectric properties of ferroelectric perovskite oxides, to act as a chemical diffusion barrier, and to prevent fatigue [16,17,23]. However, if the substrate is much thicker than the film, the mechanical properties and stress state of the piezoelectric layer stack system are substrate-dominated.…”
Section: Of 13mentioning
confidence: 99%
“…8. The process starts with the preparation of the precursor solution from Ba and Sr carboxylates, usually acetates, and Zr and Ti alkoxides, mostly propoxides and butoxides (Chen et al 2016;Chi et al 2013Chi et al , 2014Huang et al 2016;Li et al 2013Li et al , 2015cLin et al 2012;Wang et al 2014aWang et al , 2015. In most of the cases, acetic acid and 2-methoxyethanol are used as solvents.…”
Section: Chemical Solution Deposition Of Bzt-bct-based Filmsmentioning
confidence: 99%
“…Some groups reported the existence of a metastable pyrochlore phase (Chen et al 2016;Chi et al 2014;Kang et al 2012). Kang et al found that by modifying the solution chemistry, the fraction of the pyrochlore phase in BZT-0.5BCT films could be reduced.…”
Section: Chemical Solution Deposition Of Bzt-bct-based Filmsmentioning
confidence: 99%
See 1 more Smart Citation